Perkembangan Kurikulum Di Indonesia Dan Dampak Perkembangannya Terhadap Kualitas Pendidikan - Fadhila; Azzahra, Fatimah; Nur Elizanti Purba, Kezia; Bahari, Bima; Siregar, Deasy Yunita (PT. Kreasi Karya Majakata, 2023)
Curriculum development in Indonesia has experienced various changes over time. This change aims to improve the quality of education and adapt it to the needs of society and current developments. However, the impact of these curriculum developments on the quality of education needs to be analyzed critically. In this research, the literature review method was used to collect and analyze data from various related sources regarding curriculum development in Indonesia and its impact on the quality of education. Data was obtained through literature searches, academic journals and other related publications. Curriculum development in Indonesia has experienced several significant changes in the last few decades. Each change is controlled and adjusted by the Minister of Education based on certain experiences and considerations. The main aim of curriculum changes is to improve the quality of education, provide education that is relevant to society's needs, and able to compete at the global level. However, the impact of these curriculum developments can vary. On the one hand, curriculum changes can provide benefits such as increased relevance to the world of work, skills development, and integration of technology in learning. However, on the other hand, curriculum changes can also have negative impacts such as an overly heavy curriculum load, a gap between theoretical and practical subjects, and a lack of training and resources for teachers in implementing the new curriculum. Curriculum changes can also affect the education system in general, including learning methods, evaluation and further curriculum development. Therefore, careful assessment of the impact of curriculum changes on the quality of education needs to be carried out continuously to ensure the desired results are achieved. Curriculum development in Indonesia is an ongoing process in order to improve the quality of education. In making these changes, it is important to consider the impacts, both positive and negative. Evaluation of curriculum changes and close supervision are needed to ensure that the education system is able to provide quality and relevant education for students.